Research on generation scheduling mechanism of interconnected power system based on runoff forecast - Jiang, Shiming; wu, Ping; Peng, Xuhong; Tang, Yibo (Frontiers in Energy Research, 2022)
In order to reduce power energy consumption and ensure the sustainable development of resources, a research on the generation scheduling mechanism of interconnected power systems based on runoff forecasting is proposed. First, by studying energy-saving power generation scheduling and using the average distribution method, there will be a lot of energy consumption and pollution emissions, so it is necessary to formulate a reasonable power generation scheduling plan; secondly, the medium and long-term runoff forecasting method is analyzed, and artificial neural networks are used to select appropriate hidden nodes Finally, the economic characteristics of the two-stage power generation of the hydropower station are explored, and the marginal benefit of the water level storage capacity and the total power generation is obtained by combining the current operating status and forecast information of the reservoir. Through experiments, it is proved that the method in this paper can better predict the power generation scheduling mechanism of hydropower stations, and the annual power generation of the optimized scheduling is 1.92% higher than that of conventional scheduling, which has significant advantages, ensuring the reasonable distribution of power resources and preventing unnecessary waste.